The world of Giotto, c. 1267-1337 - Eimerl, Sarel; Time-Life Books ([Amsterdam, Netherlands] Time-Life Books (Nederland) B.V., 1967)
The life and times of the great Italian artist of the early Middle Ages.
The conquest of form -- The painter's craft -- Ferment in Tuscany -- A boy from the hills -- The masterwork -- Strenuous decades -- Giotto the architect -- A time of affliction.
Includes bibliographical references (pages 193-194) and index.
Keywords: Giotto di Bondone -- 1266?-1337.